Sustainable transport : planning for walking and cycling in urban environments - Tolley, R. S. 1946- (Woodhead Publishing in environmental management., 2003)
This important and wide-reaching study provides a comprehensive guide to the implementation of sustainable transport initiatives worldwide. Through a wide range of case studies from Europe, North America and Australia. Sustainable transport shows how practical schemes, infrastructure developments and educational support can provide an alternative to the growing congestion in many urban environments.